(untitled) (Eurasian Journal of Philology Science and Education, 2018)
In the methods of teaching of the state language linguistics direction in learning language became a special object of study and has been studied in various aspects. Practical examples of this position in the development of professional communication skills of the future specialist served as the basis for the article. Today it is a popular time to develop and study linguistics direction and methodological basis thoroughly, to teach professional language skills and develop the infrastructure of teaching the state language. The article proposes to teach the language with the help of linguistics direction to contact closely with the rich culture of Kazakh people to familiarize with the heritage and form it as a legacy of ancestors for the future generation. The life examples given in the article prove that this method provides a full opportunity for a systematic increase in the level of language learning, since through language humanity learns not only itself, but also the world around it. The essence of the spiritual existence of the nation and cultural values of the people is transmitted from generation to generation directly through the art of speech. Through this position, the student can more clearly and deeply convey their thoughts. In the materials of classes the cultural heritage of the Kazakh people should be considered not only for cognitive purposes, but also as a means of professional, socio-political significance for its future development as a fully developed, spiritually rich person.